PENERAPAN MULTIMEDIA INTERAKTIF POWER POINT PADA MATA DIKLAT DASAR DAN PENGUKURAN LISTRIK - oriza candra; Elfizon Elfizon; Syaiful Islami; Doni Tri Putra Yanto (PTE FTK UIN Ar-Raniry, 2020)
The purpose of this study is to seek to improve the learning outcomes of students using interactive multimedia Power Point work on the subjects of Basic learning and Electrical Measurements Work in class X TIPTL 2 SMKN 1 Padang. This type of study is a quasi-experiment. Students of class X TITL 2 Padang 1 SMKN were collected in the 2016/2017 school year consisting of 30 students as research subjects. Collecting data in this study using the test results to learn pre and post objective be about 30 items to 30 items for pre- and post. The test questions that will be used first on the tests to determine the validity, reliability, difficulty index, and different power test questions. Data were analyzed using Gain Score. The average value of the pre-test before deploying interactive multimedia Power Point is 58.5 and average values applied after the interactive Power Point post-test media is 79. Hence Gain score calculation means of learning results of students increase 0478 in the average category. It can be concluded that the interactive multimedia Power Point application can improve the results student of class X TITL 2 SMK 1 Padang on topics Basic learning and Electrical Measurements.